THE IMPORTANCE OF DIGITAL TECHNOLOGIES IN DEVELOPING COMPETENCE IN TECHNOLOGICAL EDUCATION - Koklenova, Muhayyo Aralbaevna; Davletmuratov, Boribay Koptleuovich (SCIENCE and SOCIETY, 2026)
This article examines the role and importance of digital technologies in developing students’ competencies in technological education. It highlights the opportunities for enhancing independent thinking, practical skills, and problem-solving abilities through the use of digital tools. The effectiveness of implementing innovative approaches in the educational process is also substantiated.
Keywords: competence; technological education; digital technologies; ICT; innovative learning; interactive methods; independent thinking; practical skills